Evaluation of district mental healthcare plans: The PRIME consortium methodology. (January 2016) - De Silva, Mary J.; Rathod, Sujit D.; Hanlon, Charlotte; Breuer, Erica; Chisholm, Dan; Fekadu, Abebaw; Jordans, Mark; Kigozi, Fred; Petersen, Inge; Shidhaye, Rahul; Medhin, Girmay; Ssebunnya, Joshua; et al.
Abstract : Background: Few studies have evaluated the implementation and impact of real-world mental health programmes delivered at scale in low-resource settings. Aims: To describe the cross-country research methods used to evaluate district-level mental healthcare plans (MHCPs) in Ethiopia, India, Nepal, South Africa and Uganda. Method: Multidisciplinary methods conducted at community, health facility and district levels, embedded within a theory of change. Results: The following designs are employed to evaluate the MHCPs: (a) repeat community-based cross-sectional surveys to measure change in population-level contact coverage; (b) repeat facility-based surveys to assess change in detection of disorders; (c) disorder-specific cohorts to assess the effect on patient outcomes; and (d) multilevel case studies to evaluate the process of implementation. Conclusions: To evaluate whether and how a health-system-level intervention is effective, multidisciplinary research methods are required at different population levels. Although challenging, such methods may be replicated across diverse settings.